Locating the Vanishing Point: Style in Literature, Architecture and Beyond - Donald K. Hedrick (Oz, 1980)
An Anecdote. As it so happened, I was traveling on a vacation with my family, and stopped for lunch at one of the identifiable feature of the modern highway, a Nickerson Farms restaurant…